The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/agronomy11020247
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Granular Organic Fertilizer Application by Centrifugal Spreader

Abstract: There is no specialized equipment designed to spread granular cylindrical organic fertilizer in the soil. There are also no rational recommendations available on how to spread this type of fertilizer. Mineral fertilizer spreaders are most often used for spreading granulated organic fertilizer. However, these fertilizers are significantly different from mineral fertilizers. Due to these differences, organic granular fertilizers often are spread unevenly, and the fertilizer does not reach the required working wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…It was found that, to spread the fertilizer dosage norms of 600, 800, and 1000 kg ha −1 , it is necessary to drive at a relatively low speed. Other scientific studies have found that, to achieve a more uniform distribution of cylindrical granules, it is important to increase the granule size by increasing the granule spreading flow [15], because the aerodynamic properties are greatly influenced by the size and mass of granulated fertilizers [34]. From the results of the granulated organic fertilizer spreading, using a fertilizer dosage norm of 1000 kg ha −1 and the spreader moving at a speed of 5 km h −1 (Figure 16), we can see that slightly different experimental results were obtained here compared to the results presented in Figures 12 and 15.…”
Section: Experiments Under Field Conditions and Simulation Spread Of ...mentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that, to spread the fertilizer dosage norms of 600, 800, and 1000 kg ha −1 , it is necessary to drive at a relatively low speed. Other scientific studies have found that, to achieve a more uniform distribution of cylindrical granules, it is important to increase the granule size by increasing the granule spreading flow [15], because the aerodynamic properties are greatly influenced by the size and mass of granulated fertilizers [34]. From the results of the granulated organic fertilizer spreading, using a fertilizer dosage norm of 1000 kg ha −1 and the spreader moving at a speed of 5 km h −1 (Figure 16), we can see that slightly different experimental results were obtained here compared to the results presented in Figures 12 and 15.…”
Section: Experiments Under Field Conditions and Simulation Spread Of ...mentioning
confidence: 99%
“…Researchers analyzing the simulation of poultry manure granular fertilizers found that, for a cylindrical granule spreading dosage of 200 g s −1 , the distribution of particles with a diameter of 4 mm is more even than that of the ones of 6 mm in diameter. At a granule spreading dosage norm of 400 g s −1 , the distribution of 6 mm diameter particles is more uniform than for 4 mm ones [15]. Experimental studies have shown that cattle manure granules are spread more evenly over the soil surface than meat and bone meal granules.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Analysis of the simulation results of granular organic fertilizer spreading showed that at a feed flow of granular organic fertilizer of 200 g s −1 , the distribution of pellets with the diameter of 4 mm was more even. At a feed flow of 400 g s −1 , organic fertilizer pellets with the diameter of 6 mm were more evenly distributed [28].…”
Section: Introductionmentioning
confidence: 99%
“…Among several vegetation indexes that can be calculated, NDVI (Normalised Difference Vegetation Index) and NDWI (Normalised Difference Water Index) have some practical advantages. In fact, NDVI can be applied to evaluate the plant photosynthetic activity and, therefore, its vegetative vigour and soil coverage during growth phases, so that it is measured by optical sensors (e.g., Arvatec OptRx and Trimble GreenSeeker) for planning fertilisation [12,[32][33][34][35][36][37] and irrigation. Therefore, NDVI mapping remains the most affordable way to easily and objectively obtain vineyard spatial information [3], as this index has proved to be a useful tool for monitoring crop yield [18] and table grape quality characteristics [14].…”
Section: Introductionmentioning
confidence: 99%